Pioneer Rocketry - 2019 Midwest High-Power Rocket Competition - Zabel, Nathaniel; Michek, Nathaniel; Geier, Zach; Lee, Brian; Kammann, Erin; Underwood, Robert (Proceedings of the Wisconsin Space Conference, 2020)
The Minnesota Space Grant Consortium hosts the Midwest High-Power Rocket Competition every year. This year the competition involved efficient supersonic flight. Each team needed to design a rocket that would undergo two flights. The first launch was on a competition provided motor with the goal of maximizing velocity and altitude. The second launch was on a team-selected motor, with the goal of reaching supersonic flight on the lowest impulse motor possible. A custom sensor suite was required, and additional points were awarded for including custom telemetry. Pioneer Rocketry’s rocket this year, Man That Thing’s Tiny (MT3), was designed to be as small as possible while being stable and safe. Flying a minimum diameter rocket presented many challenges that prompted the team to make several unorthodox design choices. At the competition launch, MT3’s first flight was very close to the simulation. Unfortunately the rocket was not recovered after the second flight.